An Evaluation of Industry Relationships Among Contributors to AAOS Clinical Practice Guidelines and Appropriate Use Criteria. (17th January 2018) - Checketts, Jake X.; Cook, Courtney; Vassar, Matt
Abstract : Background: A long-standing relationship between orthopaedic surgeons and industry has made financial conflicts of interest a concerning issue. Research supports that financial conflicts of interest can influence both medical research and clinical practice. Financial conflicts of interest may also influence clinical practice guideline recommendations and their corresponding appropriate use criteria. Because of the influential nature of these guidelines, it is imperative that care be taken to minimize bias during guideline development. Methods: We retrieved clinical practice guidelines and their corresponding appropriate use criteria from the American Academy of Orthopaedic Surgery that were published or revised between 2013 and 2016. We extracted industry payments received by physicians using the Centers for Medicare & Medicaid Services Open Payments database. We then evaluated the value and types of these payments. We also used these data to determine whether disclosure statements were accurate and whether guideline development was in adherence with the Institute of Medicine's (IOM's) standards. Results: Of the 106 physicians that were evaluated, 85 (80%) received at least 1 industry payment, 56 (53%) accepted >1, 000, and 35 (33%) accepted >10, 000. Financial payments amounted to a mean of 93, 512 per physician. Total reimbursement for the 85 clinical practice guideline and appropriate use criteria contributors was 9, 912, 309. We found that disclosure statements disagreed with the Open Payments data and that the IOM standards were not completely enforced. Conclusions: Clinical practice guideline and appropriate use criteria contributors received substantial payments from industry, many disclosure statements were inaccurate, and the IOM standards were not completely met. Clinical Relevance: Clinical practice guidelines and appropriate use criteria are critical for practicing evidence-based medicine. If financial conflicts of interest are present during their development, it is possible that patient care may be compromised.